A micromachined ultra‐wide stopband lowpass filter based on stepped impedance resonator loaded T‐shaped structure. Issue 12 (2nd November 2022) - Liang, Ruihua; Guo, Cheng; Yang, Qian; Shi, Guanghua; Wang, Zhen; Zhang, Anxue
Abstract: This article presents an additively manufactured micro‐coaxial lowpass filter with ultra‐wide stopband suppression. To achieve a wide stopband response, two‐stage stepped impedance resonator loaded T‐shaped structures are used to substitute the low impedance transmission lines in the lowpass filter prototype to generate extra transmission zeros in the stopband. Shunt open‐ended stubs are introduced to the structure in flexible positions to further strengthen the suppression at specific frequency points. The filter is designed with 22 GHz passband and the 20 dB stopband suppression bandwidth over 300 GHz. The micro‐coaxial lowpass filter structure was fabricated based on additive metal micro‐manufacturing process with the rectangular cross‐section dimensions of 0.5 mm × 0.5 mm (300 GHz cutoff frequency). To facilitate the measurement, pair of coax‐to‐CPW transitions are added at the input/output ports. The measurement results show excellent agreement from DC‐110 GHz (limitation of the measurement device), with insertion loss of 1.05 dB at the cutoff frequency f c, which validates the design.